1998
DOI: 10.1073/pnas.95.26.15412
|View full text |Cite
|
Sign up to set email alerts
|

A lineage-specific protein kinase crucial for myeloid maturation

Abstract: To identify genes involved in macrophage development, we used the differential display technique and compared the gene expression profiles for human myeloid HL-60 leukemia cell lines susceptible and resistant to macrophage maturation. We identified a gene coding for a protein kinase, protein kinase X (PRKX), which was expressed in the maturation-susceptible, but not in the resistant, cell line. The expression of the PRKX gene was found to be induced during monocyte, macrophage, and granulocyte maturation of HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 41 publications
2
39
0
5
Order By: Relevance
“…To determine in which cellular compartment PrKX and Smad6 reside during macrophage differentiation, we separated the nuclear and cytoplasmic fractions of HL-60 cells that were either untreated or treated for 6 or 24 h with PMA. Western blotting of the resultant lysates (Figure 4) demonstrated that PrKX was induced by PMA as has been reported previously (Semizarov et al, 1998). In contrast, Smad6 was constitutively expressed and its levels did not change as a result of PMA treatment.…”
Section: Prkx Activity During Hl-60 Differentiation D Glesne and E Husupporting
confidence: 81%
See 4 more Smart Citations
“…To determine in which cellular compartment PrKX and Smad6 reside during macrophage differentiation, we separated the nuclear and cytoplasmic fractions of HL-60 cells that were either untreated or treated for 6 or 24 h with PMA. Western blotting of the resultant lysates (Figure 4) demonstrated that PrKX was induced by PMA as has been reported previously (Semizarov et al, 1998). In contrast, Smad6 was constitutively expressed and its levels did not change as a result of PMA treatment.…”
Section: Prkx Activity During Hl-60 Differentiation D Glesne and E Husupporting
confidence: 81%
“…PrKX activity during HL-60 differentiation D Glesne and E Huberman deficient in PMA-resistant HL-60 cells (Semizarov et al, 1998). We determined that PrKX gene expression was induced during differentiation of HL-60 cells into macrophages by PMA, into monocytes by 1, 25-dihydroxy vitamin D3 and into granulocytes by ATRA as well as in peripheral blood granulocytes but not in lymphocytes (Semizarov et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations